2019
DOI: 10.7762/cnr.2019.8.1.55
|View full text |Cite
|
Sign up to set email alerts
|

Effect of High β-glucan Barley on Postprandial Blood Glucose Levels in Subjects with Normal Glucose Tolerance: Assessment by Meal Tolerance Test and Continuous Glucose Monitoring System

Abstract: The effect of white rice (WR) mixed with high β-glucan-containing barley at 50% on improvement of postprandial blood glucose levels was assessed by meal tolerance test and continuous glucose monitoring (CGM) in 15 healthy subjects with normal glucose tolerance (age 31.6 ± 12.9 years old, 4 males and 11 females). A meal tolerance test (500 kcal) was conducted using 2 types of test meals: a test meal only with WR and a test meal WR mixed 50% barley, and the side dish was the same in both meals. Blood glucose lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 30 publications
3
13
0
Order By: Relevance
“…A previous study reported that intake of high β-glucan barley led to reduction in visceral fat [17]. Our previous study showed that high β-glucan barley suppressed plasma glucose level elevation and oxidant stress after meals in subjects with normal glucose tolerance [18].…”
Section: Introductionmentioning
confidence: 86%
“…A previous study reported that intake of high β-glucan barley led to reduction in visceral fat [17]. Our previous study showed that high β-glucan barley suppressed plasma glucose level elevation and oxidant stress after meals in subjects with normal glucose tolerance [18].…”
Section: Introductionmentioning
confidence: 86%
“…γ -PGA is a viscous substance [ 3 ], and its content is approximately eight-fold higher in HPGA natto than in LPGA natto. β-glucan, a water-soluble dietary fiber, has high viscosity [ 6 ] like γ -PGA. β-glucan increases the viscosity of the food bolus and slows down the movements in the digestive tract, which delays gastric emptying and absorption [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…β-glucan, a water-soluble dietary fiber, is a highly viscous substance [ 5 ] similar to γ -PGA. Higa et al reported that postprandial glucose levels are suppressed in response to a mixture of high-β-glucan barley with white rice (WR) 30 min after test meal loading in healthy participants [ 6 ]. Ames et al compared the postprandial glucose levels after loading with tortillas prepared from flours with various β-glucan contents and revealed a greater decrease in the percent change in glucose levels from the baseline to 30 min after high-β-glucan treatments than that observed in response to low- and medium-β-glucan treatments [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…WG barley and isolated barley β-glucan have been broadly studied for their ability to impact diabetic markers among diabetic, obese or overweight, mildly diabetic, and healthy individuals, with varying degrees of success (Chillo et al, 2011;Higa et al, 2019;Liu et al, 2015;Tosh 2013). Most of these studies also enriched or incorporated WG barley and β-glucan into various food like bread, porridge, tortillas, and pasta while evaluating their ability to exert glycemic control.…”
Section: Anti-diabetic Effects Of Barley: Evidence From Human Studiesmentioning
confidence: 99%